REVIEW OF THE GENUS CHAUHANELLUS (YOUNG, 1967) BYCHOWSKY AND NAGIBINA, 1969 WITH A REPORT ON A NEW SPECIES FROM FRESHWATER FISHES OF MEERUT (U.P.), INDIA - RASTOGI, PRAGATI; KUMAR, KAPIL; SINGH, H. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
A new species of the genus Chauhanellus (Young, 1967) Bychowsky and Nagibina, 1969 is described from the gills of two different fishes viz., Wallago attu (family: Siluridae) and Mystus tengara (family: Bagiridae) from Meerut. It is the first report from a freshwater fish. Probable reasons for the appearance of this genus in freshwater fish are discussed in detail together with the zoogeographical distribution of this genus across the globe.